A description of kinship care placements in Nseleni, Richards Bay district. - Mdletshe, Peggy Zethu. (2008)
This study described kinship care placement in the Nseleni area. The study aims to describe the type of care in kinship foster care placements in the Nseleni area, Richards Bay. The objectives of the study were to investigate the physical and material circumstances of the families, to explore the psycho-social needs of the children, to explore whether or not the kinship carer is experiencing physical and emotional problems and to identify support systems available to kinship carers. The study was guided by the ecosystems perspective. This perspective attempts to appreciate and understand people in their environment. The ecosystems perspective was pertinent in this study as it provided a framework for understanding the individual, family, community and society context in which kinship carers operate. A quantitative descriptive (survey) approach guided this study. This design is useful for describing the characteristics of a large population and therefore it was an appropriate design for this study which aimed at describing how children in kinship care are being cared for. The sample comprised of 30 kinship carers who were respondents. Probability sampling was used to ensure representativeness and that all the members of the identified population had an equal chance of being selected. Structured interview questionnaires were personally administered to the respondents. Data was analyzed manually. Each of the questions was recorded in the manual table for data entry. All variables were added and checked. The totals were converted into percentages for easy calculation and analysis. Using Microsoft excel, tables and figures were formulated. === Thesis (M.A.)-University of KwaZulu-Natal, Durban, 2008.